Factors Influencing E-Commerce Purchase Decisions in Rural Areas: A Study on User Convenience and Consumer Trust - Pratiwi, Vina Andita; Mirahwati, Indri; Fitralisma, Gian; Nawawi, Rusto (Papanda Publisher, 2025)
In the modern era, the advancement of information and communication technology has significantly impacted various aspects of human life, including consumption behavior and business practices. The internet, as a core technological tool, has become an inseparable part of daily activities. E-commerce, particularly platforms like Shopee, has gained immense popularity in Indonesia, providing easy and efficient online shopping experiences. This study examines the influence of two key factors, ease of use and consumer trust, on purchase decisions in e-commerce, specifically in the rural community of RW 07, Desa Sirnasari, Tasikmalaya. Using a quantitative approach, the research employs associative causal methods and data collection through interviews, observations, questionnaires, and literature studies. The findings reveal that both ease of use and consumer trust significantly affect purchase decisions, with trust having a more substantial impact. The study's results highlight that improving user-friendliness and transparency can enhance consumer trust and purchasing behavior. This research contributes to the literature by offering insights into consumer behavior in rural areas and provides practical recommendations for e-commerce platforms to improve services. Future research can explore other influencing factors such as price, social influences, and product quality.